2017
DOI: 10.3823/814
|View full text |Cite
|
Sign up to set email alerts
|

Resistance profiles and biofilm formation of coagulase negative staphylococci isolated from clinical specimens in a tertiary care hospital in Palestine

Abstract: Background: Coagulase-negative staphylococci (CoNS) represent one of the major resistant nosocomial pathogens where its biofilmrelated infections often fail to respond to antibiotic chemotherapy. Here, we studied the resistance profiles and biofilm formation in CoNS isolates from clinical specimens at Al Shifa hospital in Gaza, Palestine. Methods:This study was carried out from March to July 2013 and included 81 clinical isolates. Identification and antibiotic susceptibility testing were performed using VITEK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…These findings were consistent with those of Palestine and Ethiopia. 31,32 Interestingly, all resistant genotypes and their combinations were observed in isolates from the skin and soft tissues in the present study. In addition to skin and soft tissue infection samples, genital tract samples, such as high vaginal swab and semen, also exhibited high level of antibiotic resistance.…”
Section: Discussionsupporting
confidence: 53%
“…These findings were consistent with those of Palestine and Ethiopia. 31,32 Interestingly, all resistant genotypes and their combinations were observed in isolates from the skin and soft tissues in the present study. In addition to skin and soft tissue infection samples, genital tract samples, such as high vaginal swab and semen, also exhibited high level of antibiotic resistance.…”
Section: Discussionsupporting
confidence: 53%
“…Table 7 shows the resistance rate of S. aureus in these studies. Recent published studies in 2017 and 2020, have recorded a higher resistance rates when compared to a study reported in 2015 [41][42][43].…”
Section: Resistance Pattern Against Methicillin Among Staphylococcus Spp Isolated From Clinical and Hospital Setting Samplesmentioning
confidence: 66%
“…Few studies has reported that Extended-Spectrum Beta-Lactamase (ESBL) production as well as colistin resistance among Enterobacteriaceae isolates in Gaza becomes more prevalent in recent years [23,32,35]. Additionally, MRSA was highly emerged either in clinical samples or hospital environment in Gaza strip [34,[41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations